A descriptive analysis of overlapping in attitudinal terms in two types of interview - Romero Valenzuela, Ámbar (Lenguas Modernas, 2010)
In conversational studies, various authors have noticed that simultaneous talk does not only occur as the result of an unintentional overlapping transition but also as the result of intentional cutting-in while the current speaker has not yet reached the proximity of the end of their turn. Following this perspective, the nature of the roles of interviewer and interviewee are explored in two types of broadcast discourse. Focusing on excerpts taken from a political interview (Hardtalk) and a talk show (The Oprah Winfrey show) this study intends to account for the attitudinal processes that embody these two speech events by comparing the management of turn taking as seen in the phenomenon of overlapping. The main objectives are to observe and describe how collaborative or non-collaborative the interviewer and interviewee’s attitudes are as reflected in the negotiation of turns and how this may be influenced by the type of TV genre. It is proposed that the political interview with its conflicting character differs in the management of turn-taking behaviour from non-conflictive interviews such as talk shows, where overlaps, being collaborative in nature, display positive attitudes such as agreement, willingness to give detail, and acknowledgement from both the interviewer and interviewee.